Long-term ambient air pollution and lung function impairment in Chinese children from a high air pollution range area: The Seven Northeastern Cities (SNEC) study. (August 2016) - Zeng, Xiao-Wen; Vivian, Elaina; Mohammed, Kahee A.; Jakhar, Shailja; Vaughn, Michael; Huang, Jin; Zelicoff, Alan; Xaverius, Pamela; Bai, Zhipeng; Lin, Shao; Hao, Yuan-Tao; Paul, Gunther; et al.
Abstract: Epidemiological studies have reported inconsistent and inconclusive associations between long-term exposure to ambient air pollution and lung function in children from Europe and America, where air pollution levels were typically low. The aim of the present study is to examine the relationship between air pollutants and lung function in children selected from heavily industrialized and polluted cities in northeastern China. During 2012, 6740 boys and girls aged 7–14 years were recruited in 24 districts of seven northeastern cities. Portable electronic spirometers were used to measure lung function. Four-year average concentrations of particulate matter with an aerodynamic diameter ≤10 μm (PM10 ), sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and ozone (O3 ) were measured at monitoring stations in the 24 districts. Two-staged regression models were used in the data analysis, controlling for covariates. Overall, for all subjects, the increased odds of lung function impairment associated with exposure to air pollutants, ranged from 5% (adjusted odds ratio [aOR] = 1.05; 95% confidence interval [CI] = 1.01, 1.10) for FVC < 85% predicted per 46.3 μg/m 3 for O3 to 81% (aOR = 1.81; 95%CI = 1.44, 2.28) for FEV1 < 85% predicted per 30.6 μg/m 3 for PM10 . The linear regression models consistently showed a negative relationship between all air pollutants and lung function measures across subjects. There were significant interaction terms indicating gender differences for lung function impairment and pulmonary function from exposure to some pollutants ( P < 0.10). In conclusion, long term exposure to high concentrations of ambient air pollution is associated with decreased pulmonary function and lung function impairment, and females appear to be more susceptible than males. Graphical abstract: Highlights: The associations between ambient air pollution and lung function are inconsistent. Few studies assessed such associations in children from a high air pollution area. We included a large population of 6740 Chinese children from seven cities of China. Increased odds of lung function impairment associated with exposure to air pollutants. The relationship between pollutants and lung function was modified by gender.